Application of infrared thermography for the determination of the overall heat transfer coefficient (U-Value) in building envelopes - Fokaides, Paris A.; Kalogirou, Soteris A. (My University, 2011)
Infrared (IR) thermography constitutes a reliable measurement method for the determination of spatially resolved surface temperature distributions. IR thermography may be used for several research problems, applications, and measurement environments with a variety of physical arrangements. In this work the results of the determination of the overall heat transfer coefficient (U-Value) with the use of IR thermography for building envelopes are presented. The obtained U-Values are validated by means of measurements performed with the use of a thermohygrometer for two seasons (summer and winter), as well as with the notional results provided by the relevant EN standard. Issues related to the applicability of the method due to the non-steady heat transfer phenomena observed at building shells are also discussed. A more precise validation of the proposed technique was also performed with the use of heat flux meters. The percentage absolute deviation between the notional and the measured U-Values for IR thermography is found to be in an acceptable level, in the range of 10–20%. Finally, a sensitivity analysis is conducted in order to define the most important parameters which may have a significant influence on the measurement accuracy
Keywords: Heat--Transmission; Thermography; Solar buildings; Energy